1996
DOI: 10.1063/1.362631
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity in high-frequency plasmas

Abstract: A dense, lowtemperature, plasma target driven by an immersed, inductive antenna AIP Conf.The electrical conductivity is an important parameter in understanding the mechanism by which power is coupled to a radio-frequency ͑rf͒ discharge plasma, as well as in determining the external electrical characteristics of the discharge. We present the results of computations of the resistive and reactive components of the collisional impedance of an argon plasma at 13.56 MHz. The plasma conductivity is computed from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 22 publications
(14 reference statements)
0
41
0
Order By: Relevance
“…͑3͒ to account for the dependence of electron collision frequency on the electron velocity ͑energy͒ and shape of the electron spectra as in Ref. 5. Integrating v 1 with respect to time we obtain:…”
Section: ͓S0003-6951͑00͒03216-2͔mentioning
confidence: 99%
“…͑3͒ to account for the dependence of electron collision frequency on the electron velocity ͑energy͒ and shape of the electron spectra as in Ref. 5. Integrating v 1 with respect to time we obtain:…”
Section: ͓S0003-6951͑00͒03216-2͔mentioning
confidence: 99%
“…Frequencies m and w are replaced by effective frequencies eff and w eff . The collision frequency m is not the same as eff when the EDF is not Maxwellian, the collision frequency is not constant for electron energy, or there is significant collisionless (or non-Ohmic) power absorption [15,16]. The values of eff and w eff can be obtained from the plasma resistivity [16] Ẽ cos =J Re ÿ1 m eff =ne 2…”
mentioning
confidence: 99%
“…Lister et al 17 and Godyak et al 18 intensively studied the effect of electron collisions on electrical conductivity in rf plasmas and found that both the reactive and resistive components of the plasma impedance are influenced by the collisions.…”
Section: A Calculation Of the Azimuthal Electric Fieldmentioning
confidence: 99%